Utilization of Buffalo Manure and Samosir Goat Manure on Indigofera Zollingeriana Growth - Indria Ningsih; E Mirwandhono; Nurzainah Ginting; Iskandar Sembiring; N D Hanavy (Jurnal Peternakan Integratif, 2018)
This study aims to look at the effect of buffalo and goat manure on the growth of Indigofera zollingeriana plants. This research was carried out in Parlondut Village, Pangururan Subdistrict, Samosir Regency, North Sumatra from March to May 2018. The design used in this study was a Completely Randomized Design with 4 replications. P0 = Buffalo Cage Fertilizer 25% + 75% Top Soil Soil, P1 = Buffalo Cage Fertilizer 50% + 50% Top Soil Soil, P2 = Buffalo Cage Fertilizer 75% + 25% Top Soil Soil, P3 = 25% Goat Cage Fertilizer + 75% Top Soil Soil, P4 = Goat Cage Fertilizer 50% + 50% Top Soil Soil and P5 = Goat Cage Fertilizer 75% + 25% Top Soil Soil. The variables observed were plant height, number of leaves, number of stems, stem diameter and leaf width. The results showed that the application of manure from goats had a significant effect on the parameters of the study, namely plant height, number of leaves, number of branches and stem diameter. In conclusion, the increasing dosage of fertilization with goat manure on Indigofera zollingeriana plants, the results are getting better.